Organization-Methodological Bases of Practice of the Students-Philologists at University - Nataliia Kazakova (Pedagogical Discourse, 2016)
Organization-methodological bases of continuous practice of the students-philologists at university (from the experience of practice organization at the faculty of primary education and philology on speciality «Philology. Ukrainian Language and Literature» in Khmelnytskyi Humanitarian-Pedagogical Academy) have been determined in the article. To them belong: determination of the goal, which means succession in realization of tasks of self-actualization, self-organization, self-realization, self-analysis and self-evaluation of the activity; choice of the content and fulfillment of the activity of all subjects of practice according to the stages (propaedeutic, organization-research, profession-oriented and scientific-research);re-orientation of the students’ activity from didactic into developing and problem-searching methods of work with schoolchildren, which allow mastering of pedagogical profession not at the reproductive, but at the creative level. It is accentuated that the expected results of the practice should provide for the well-formedness of professional-pedagogical competence of the future philologist of Ukrainian language and literature, which includes the ability to turn into productive interaction in its theoretical and practical expression literary studying, linguistic, psychological, pedagogical, didactic, methodological, communicative components. Key words: professional-pedagogical competence of the future philologist, practice, organizational-methodological bases, goal and result of practice.